2020
DOI: 10.3390/polym12112681
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization of Nanocomposite Joints Based on Biomedical Grade Polyethylene under Cyclical Loads

Abstract: Polymeric joints, made of biomedical polyethylene (UHMWPE) nanocomposite sheets, were welded with a diode laser. Since polyethylene does not absorb laser light, nanocomposites were prepared containing different percentages by weight of titanium dioxide as it is a laser absorbent. The joints were first analyzed with static mechanical tests to establish the best percentage weight content of filler that had the best mechanical response. Then, the nanocomposites containing 1 wt% titanium dioxide were selected (whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In addition, the absorption of isocyanate does not appear at 2275 cm −1 due to the complete reaction of the isocyanate with the polyol and water to form urethane and carbon dioxide bonds, respectively [ 40 ]. The peaks near the wave number of 2950 cm −1 are associated with the vibration of the functional group in the carbon chains –CH 2 -and –CH [ 39 , 42 ]. The sharp peak at the wave number 1717 cm −1 is linked to the urethane function and the carbonyl (C = O) of the functional group existing in the urethane bond [ 41 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the absorption of isocyanate does not appear at 2275 cm −1 due to the complete reaction of the isocyanate with the polyol and water to form urethane and carbon dioxide bonds, respectively [ 40 ]. The peaks near the wave number of 2950 cm −1 are associated with the vibration of the functional group in the carbon chains –CH 2 -and –CH [ 39 , 42 ]. The sharp peak at the wave number 1717 cm −1 is linked to the urethane function and the carbonyl (C = O) of the functional group existing in the urethane bond [ 41 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 1093 cm −1 is attributed to the etheric vibration of the C-O group [ 40 , 42 ]. The peak at 1531 cm −1 is due to the C-N and N-H groups (Amides II) [ 39 ]. The average intensity signal observed around 1596 cm− 1 belongs to the aromatic vibration C = C [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the proposed method should be frequently used in un-welded and welded structures because it is easy to operate, is reliable, and is safe. Visco et al [ 15 ] analyzed weld joints using static mechanical tests. The results revealed that the joints had an appreciable resistance to fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, particular attention was given to the study of the fatigue behavior of the polyurethane-CNF sponges. Fatigue properties of polymers and composites still represent a timely topic, which has not been widely investigated [ 38 ]. However, in many fields of application, the response of these materials to dynamic forces allows one to obtain useful information [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%